PRODUK PARIWISATA BERBASIS EKOLOGI DI HA LONG BAY, VIETNAM - Hamidah, Siti (Jurnal Kepariwisataan Indonesia : Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Ha Long Bay is one of eminent tourist destinations in Vietnam. This destination has been attaining international recognition for its landscape beauty and uniqueness, besides its  geological values inside the region. There has been an increasing number on tourist arrivals since Ha Long Bay declared as UNESCO Heritage Sites in 1994. However, the increasing of tourist visitors teamed with some problematic issues related to environment and certain conflicts between tourism and protection to natural heritage. This paper discussed the issues and government efforts to manage Ha Long Bay tourist destination. Research Method used is qualitative and descriptive data analysis. Data sources derived from primary and secondary data. The result of the research shows that Vietnamese Government has issued Strategy on Vietnam?s Tourism Development until 2020, Vision to 2030 and Vietnam?s Sustainable Development Strategy for 2011-2020. Ha Long Bay Management Board becomes the leading sector in Ha Long Bay management, which has been doing partnership with international organizations, involving local government, private sectors and local communities. These become an important point for the implementation of Action Plan for Preservation of the Ha Long Bay Heritage, to achieve quality tourism and sustainability of Ha Long Bay environment.